Conversation and Its Communicative Impact on Teaching Arabic to Non-Native Speakers - Hamou Lhadj , Dehbia; Keddache, Lamia (LANGUAGE ART, 2024)
Oral conversational language education offers a distinctive opportunity for language acquisition and learning, giving the learner value and meaning to language learning, and the skills acquired are more visible, allowing him to employ the language acquired in multiple situations. It seems through experiments that the learner in this way is more positive and involved in formal linguistic practice As it has the ability to express and write den hindrances and desires to learn the second language, Which is done only by immersing itself in the surroundings of that language. Learning", the learner employs his or her linguistic asset through language communication and training in the construction of new language compositions produced spontaneously without making or costing, as it tries to employ language elements to create real linguistic communication appropriate to the social, linguistic and cultural context during linguistic and conversational practice. This topic seeks to determine the place of conversation in teaching Arabic to non-speakers, and to monitor the most important strategy for the success of the method of dialogue and conversation by referring to the role of expression and archives, and standing in the techniques followed and the way of F. Joan Gouin François is a model, and this is by tracking the analytical descriptive curriculum that allows to stand up to the conversation mechanism and reveal its importance in teaching Arabic to non-speakers. One of the outcomes we want is to focus on the continuum in Arabic language education, adopt the conversation as a way of teaching as its design and objectives approach real attitudes and drive the learner into practice by respecting the language's norms and synthesis, and create other methods aimed at consolidating the second language in particular.